Ceramics Israel. - Clark, James R.; Ceramic Artists Association of Israel; Art Focus Contemporary Israeli Art, Jerusalem 1994 (Beer Sheva : The Negev Museum, 1994)
Hefetz, Magdalena ; Morris, David ; Jacoby, Doron ; Miller, Hannah ; Una, Meira ; Aronow, Adi Adela ; Mayer, Judith ; Ben-David, Gila ; Adi, Edith ; Rubinstein, Boris ; Barel, Anat ; Sheves, Leah ; Yudell, Mark ; etc.
Ceramics Israel, The Negev Museum, Beer Sheva, 1994. Art Focus Contemporary Israeli Art, Jerusalem 1994
boek
Keywords: Israel